2017
DOI: 10.1002/anie.201705546
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Controlled, Enantioselective, and Diastereodivergent Conjugate Addition of Aldehydes to Electron‐Deficient Olefins

Abstract: A chiral-amine-catalyzed enantioselective and diastereodivergent method for aldehyde addition to electron-deficient olefins is presented. Hydrogen bonding was used as a control element to achieve unusual anti selectivity, which was further elucidated through mechanistic and computational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Since the phenylcyclopropane-based amino sulfonamide catalyst ( R , S )- 14 behaves similarly to the binaphthyl-based catalyst ( R )- 2 , utility of the phenylcyclopropane scaffold as a novel chiral motif has been evaluated in several other amine-catalyzed reactions. We found that ( R , S )- 14 was an effective catalyst for the asymmetric aminoxylation of 3-phenylpropanal with nitrosobenzene, and in situ reduction of the product with NaBH 4 gave 1,2-diol derivative 22 with excellent enantioselectivity (Scheme c). , On the other hand, use of chiral amino alcohol ( R , S )- 15 as catalyst afforded the optically enriched hydroxyamination product 23 exclusively from the same set of reactants (Scheme d). , Several chiral amine catalysts were applied to the conjugate addition of 3-phenylpropanal to nitrostyrene, and ( R , S )- 16 bearing a bulky diphenyl­(trimethylsiloxy)­methyl group provided the corresponding conjugate adduct 24 in good yield with high enantioselectivity (Scheme e). , Additionally, ( R , S )- 16 proved to be an appropriate catalyst for the conjugate addition to enone 25 , giving ketone 27 with satisfactory yield and stereoselectivity after olefination of the resulting conjugate adduct with 26 (Scheme f) …”
mentioning
confidence: 99%
“…Since the phenylcyclopropane-based amino sulfonamide catalyst ( R , S )- 14 behaves similarly to the binaphthyl-based catalyst ( R )- 2 , utility of the phenylcyclopropane scaffold as a novel chiral motif has been evaluated in several other amine-catalyzed reactions. We found that ( R , S )- 14 was an effective catalyst for the asymmetric aminoxylation of 3-phenylpropanal with nitrosobenzene, and in situ reduction of the product with NaBH 4 gave 1,2-diol derivative 22 with excellent enantioselectivity (Scheme c). , On the other hand, use of chiral amino alcohol ( R , S )- 15 as catalyst afforded the optically enriched hydroxyamination product 23 exclusively from the same set of reactants (Scheme d). , Several chiral amine catalysts were applied to the conjugate addition of 3-phenylpropanal to nitrostyrene, and ( R , S )- 16 bearing a bulky diphenyl­(trimethylsiloxy)­methyl group provided the corresponding conjugate adduct 24 in good yield with high enantioselectivity (Scheme e). , Additionally, ( R , S )- 16 proved to be an appropriate catalyst for the conjugate addition to enone 25 , giving ketone 27 with satisfactory yield and stereoselectivity after olefination of the resulting conjugate adduct with 26 (Scheme f) …”
mentioning
confidence: 99%
“…High‐resolution mass spectrometry (HRMS) data were recorded on a JMS‐700 quadrupole mass spectrometer. Catalysts 8–11 , [ 11b,16 ] ( E )‐alkyl 3‐benzoylacrylates 2bE‐2dE , [ 17 ] 2eE‐2fE , [ 18 ] 2gE , [ 19 ] 2iE , [ 20 ] 2jE , [ 21 ] 2aI , [ 17 ] 2bI‐2dI , [ 22 ] 2aM , [ 22 ] 2dM , [ 22 ] 2fM , [ 23 ] 2gM , [ 24 ] 2aT , [ 25 ] 2fT [ 26 ] were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Maruoka and coworkers used dihydroazepine‐bridged catalyst for the regio‐ and stereoselective conjugate addition of aldehydes to β‐tosyl enones with high syn selectivity and up to 94 % ee ( Figure 1 ,e ) [8] . Modifying the naphthalene backbone to a biphenyl‐based backbone and introducing substituents that can act as hydrogen bond donors, the enantioselective and diastereodivergent conjugate addition of aldehydes to electron‐deficient olefins was accomplished with high enantiomeric excess and moderate anti‐regioselectivity ( Figure 1 ,f ) [9] . Another application of azepine‐bridged biaryls and their salts is the asymmetric epoxidation of olefins ( Figure 1 ,g and 1,h ) [10–12] …”
Section: Introductionmentioning
confidence: 99%